The relationship between student engagement and teachers’ disciplinary techniques: significance for prevention practice - Богићевић, Драгана; Попопвић-Ћитић, Бранислава; Трајковић, Марија (Studies in Teaching and Education, 2025)
Modern prevention practice relies heavily on interventions aimed at strengthening protective factors, of which the importance of student engagement is increasingly emphasized in the school context. School engagement, as a multidimensional construct that includes behavioral, emotional, and cognitive components, is associated with a range of positive developmental outcomes that can be used to prevent various types of behavior problems in students. Accordingly, further scientific efforts aim to identify predictors of school engagement. Therefore, the main objective of this study is to examine the effects of disciplinary techniques used by teachers on student engagement. The sample consisted of 860 students of both genders from six secondary schools in the area of the city of Belgrade. Two scales were used for data collection - the Student Engagement Scale and the Positive and Punitive Disciplinary Techniques Scale, which are part of the Delaware School Climate Scale comprehensive instrument. The results suggest that students' engagement varies as a function of disciplinary techniques, i.e., a strong correlation was found between the use of positive disciplinary techniques and higher student engagement (r = 0.603, p < .001) and a slightly weaker correlation was found between punitive disciplinary techniques and lower student engagement (r = -0.25, p < .001). In addition, disciplinary techniques were found to have a significant impact on student engagement. In accordance with the findings obtained, it can be concluded that it would be justified to implement professional training programs for teachers that would influence the increase in the level of school engagement by strengthening positive disciplinary techniques, improving teachers' knowledge and skills, which would consequently prevent various types of student behavior problems.
Keywords: school engagement, student engagement, disciplinary techniques, prevention practice